On the role and opportunities in teamwork design for advanced multi-robot search systems - Francos, Roee M.; Bruckstein, Alfred M. (Frontiers in Robotics and AI, 2023)
Intelligent robotic systems are becoming ever more present in our lives across a multitude of domains such as industry, transportation, agriculture, security, healthcare and even education. Such systems enable humans to focus on more interesting and sophisticated tasks while robots accomplish tasks that are either too tedious, routine or potentially dangerous for humans to do. Recent advances in perception technologies and accompanying hardware, mainly attributed to rapid advancements in the deep-learning ecosystem, enable the deployment of robotic systems equipped with onboard sensors as well as the computational power to perform autonomous reasoning and decision making online. While there has been significant progress in expanding the capabilities of single and multi-robot systems during the last decades across a multitude of domains and applications, there are many promising areas for future research that shall advance the state of cooperative searching systems that employ multiple robots. In this article, several prospective avenues of research in teamwork cooperation with immense potential to the advancement of future multi-robot searching systems will be visited and discussed. In previous works we have shown that multi-agent search tasks can greatly benefit from intelligent cooperation between team members and can achieve performance close to the theoretical bound. The applied techniques can be used in a variety of domains including planning against adversarial opponents, control of forest fires and search-and-rescue missions. The state-of-the-art research on multi-robot search tasks across several selected domains of application and solution types is explained, highlighting the pros and cons of each method and serving as an up-to-date view on the current state of the discussed domains and their future challenges.